New-onset diabetes and antiretroviral treatments in HIV-infected adults in Thailand - Prakit Riyaten (2018)
Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved. Background: Use of several antiretrovirals (ARVs) has been shown to be associated with a higher risk of diabetes in HIV-infected adults. We estimated the incidence of new-onset diabetes and assessed the association between individual ARVs and ARV combinations, and diabetes in a large cohort in Thailand. Methods: We selected all HIV-1-infected, nondiabetic, antiretroviral-naive adults enrolled in the Program for HIV Prevention and Treatment cohort (NCT00433030) between January 2000 and December 2011. Diabetes was defined as confirmed fasting plasma glucose ≤126 mg/dL or random plasma glucose ≤200 mg/dL. Incidence was the number of cases divided by the total number of person-years of follow-up. Association between ARVs and ARV combinations, and new-onset diabetes was assessed using Cox proportional hazards models. Results: Overall, 1594 HIV-infected patients (76% female) were included. Median age at antiretroviral therapy initiation was 32.5 years. The incidence rate of diabetes was 5.0 per 1000 person-years of followup (95% confidence interval: 3.8 to 6.6) (53 cases). In analyses adjusted for potential confounders, exposure to stavudine + didanosine [adjusted hazard ratio (aHR) = 3.9; P = 0.001] and cumulative exposure ≤1 year to zidovudine (aHR = 2.3 vs. no exposure; P = 0.009) were associated with a higher risk of diabetes. Conversely, cumulative exposure≤1 year to tenofovir (aHR = 0.4 vs. no exposure; P = 0.02) and emtricitabine (aHR = 0.4 vs. no exposure; P = 0.03) were associated with a lower risk. Conclusions: The incidence of diabetes in this predominantly female, young, lean population was relatively low. Although stavudine and didanosine have now been phased out in most antiretroviral therapy programs, our analysis suggests a higher risk of diabetes with zidovudine, frequently prescribed today in resource-limited settings.